The universal declaration of human rights : fifty years on - Coates, Ken (Nottingham : Spokesman, 1998)
Bibliotheek François Vercammen
A paer given to the New European Left Forum which met in Athens on december 10th, 1998, the fiftieth anniversary of the signing of the universal declaration
Engels
Monografie